Burnout and job stress of anesthesiologists in the tertiary class A hospitals in Northwest China: A cross-sectional design - Yang, Guang; Pan, Lin-yuan; Fu, Xiao-li; Qing, Zhong; Dong, Bu-huai; Ye, Jiu-min (Frontiers in Medicine, 2023)
Purpose: Our purpose was to assess job stress and burnout among anesthesiologists in the Tertiary-class A hospital in Northwest China, and to analyze the possible causes and adverse consequences of increased job stress and burnout of anesthesiologists in this region and put forward suggestions in combination with the current national policies. Methods: We sent a total of 500 electronic questionnaires to all anesthesiologists practicing in the Tertiary-class A Hospital in Northwest China from 1960 to 2017 on April 2020. 336 (67.2%) questionnaires were returned and could be used for analysis. Burnout and job stress were assessed by using modified Maslach Burnout Inventory-Human Services Survey and Chinese Perceived Stress Scale, respectively. Results: First, as for emotional exhaustion, the situations of anesthesiologists with different working years and workload are different with statistical significance (P<0.05); Second, as for depersonalization, the situations of anesthesiologists with different age, professional title, working years, physical health status and workload are different(P<0.05); Third, as for personal accomplishment, the situations of anesthesiologists with different physical health status are different (P<0.05); Finally, The regression results showed that the longer the fatigue working years and the worse the physical health of anesthesiologists in Northwest China, the more likely these two factors were to cause burnout (P<0.05), as for job stress, there was a negative correlation between job stress and physical health status (P<0.05). Conclusions: Burnout and high job pressure are common among anesthesiologists in the Tertiary-class A Hospital in Northwest China. We should focus on the allocation of labor intensity, pay attention to the physical and mental health of employees, establish targeted incentive mechanism, and improve the system of promotion and income rises for grassroots doctors. This may be not only conducive to the quality of medical care for patients, but also conducive to the development of anesthesiology in China.